MANGROVE SUCCESSION IN SEGARA ANAKAN, CILACAP - Djohan, Tjut Sugandawaty (Fakultas Biologi Universitas Gadjah Mada, 2007)
The purpose of this research was to study primary and secondary succession of mangroves in Segara Anakan, a brackish water estuary, in Central Java, which experienced heavy siltation. This siltation created not only a lot of newly formed land, but also shoals which changed the pattern of tides and currents. In addition, the mangroves also experienced illegal cutting, which opened a gap in the forest. This study was carried out in 1997 at newly-formed lands and forest-gap areas, and it was compared to the 1981-1984 study. Permanent transect and quadrate plots were established across the selected areas. The result showed that almost all the mangrove areas in the Segara Anakan were disturbed. Much of the mangrove forest was rapidly converted into shrimp ponds. Primary succession occurred on mud flats of the newly formed land and on the progradation shorelines, and secondary succession occurred in the forest gap. The propagules of Sonneratia alba and Avicennia alba colonized the newly formed land. Then, as a sere developed the dominant species was A. alba. The development of a sere of mangrove pioneers on the newly formed lands was dictated not only by the heavy siltation, current and tide patterns, but also was forced by the availability of propagules and seeds in adjacent forest areas. Along the transects there were no species zonations. Acanthus ilicifolius and Derris heterophylla colonized the forest gap. Rhizopora spp. and Bruguiera spp. are endangered species in the Segara Anakan mangrove.